2021
DOI: 10.3389/fphar.2021.639475
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cystic Fibrosis: From Gene- to Cell-Based Therapies

Abstract: Prognosis of patients with cystic fibrosis (CF) varies extensively despite recent advances in targeted therapies that improve CF transmembrane conductance regulator (CFTR) function. Despite being a multi-organ disease, extensive lung tissue destruction remains the major cause of morbidity and mortality. Progress towards a curative treatment strategy that implements a CFTR gene addition-technology to the patients’ lungs has been slow and not yet developed beyond clinical trials. Improved delivery vectors are ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 139 publications
0
29
0
1
Order By: Relevance
“…Need to control the phenotype of corrected cells: type of cells, free of new mutation; safe and effective manner to engraft corrected cells into airways [45][46][47][48][49] Ataluren is a non-aminoglycoside small molecule with readthrough properties in vitro that has failed to show in vivo efficacy in phase 3 trials in cystic fibrosis [17]. More recently, ELX-02, a small eukaryotic ribosomal selective glycoside, derived from the initial glycoside core, has shown promise as a PTC readthrough therapeutic and is currently investigated in phase 2 trials in patients with cystic fibrosis caused by the G542X mutant [18].…”
Section: Mutation-specificmentioning
confidence: 99%
See 2 more Smart Citations
“…Need to control the phenotype of corrected cells: type of cells, free of new mutation; safe and effective manner to engraft corrected cells into airways [45][46][47][48][49] Ataluren is a non-aminoglycoside small molecule with readthrough properties in vitro that has failed to show in vivo efficacy in phase 3 trials in cystic fibrosis [17]. More recently, ELX-02, a small eukaryotic ribosomal selective glycoside, derived from the initial glycoside core, has shown promise as a PTC readthrough therapeutic and is currently investigated in phase 2 trials in patients with cystic fibrosis caused by the G542X mutant [18].…”
Section: Mutation-specificmentioning
confidence: 99%
“…First, cells from a patient with cystic fibrosis are isolated and manipulated in the laboratory to reprogramme them into iPSCs; then, the CFTR mutation is converted to the wildtype status, and finally, the corrected iPSCs are turned into basal airway stem cells which have the capacity to differentiate into all cell types of pseudostratified airway epithelium [46]. The last step is to engraft corrected basal cells onto the patient's basement membrane of the airway epithelium to achieve an autologous graft and replenish the airways with a fully CFTR-corrected airway epithelium [47]. Major challenges are the need to derive a pure population of airway epithelial cells from iPSCs in sufficient numbers to engraft in human airways, engrafting these cells in airways in a safe and effective manner and making sure that the corrected cells are free of integrations and somatic mutations [48].…”
Section: Cell-based Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been demonstrated that the inhibition of NMD by small molecules (SMG1i or NMDI-14) or antisense oligonucleotides (ASOs), in combination with G418 and/or CFTR modulators, rescued W1282X-CFTR function in the 16HBE cell line and primary nasal epithelial cells [30,[32][33][34]. Moreover, gene and stem cell-based therapy or genome editing by CRISPR-Cas9 are being explored in in vitro studies as therapeutic approaches for CF patients bearing nonsense mutations [35][36][37][38][39][40].…”
Section: Novel Therapies For Cfmentioning
confidence: 99%
“…New animal models and more efficacious gene transfer agents have been developed to move the field in the path to success. Several recent excellent review articles have summarized and discussed the lessons and achievements from the last 3 decades ( Cooney et al, 2018a ; Donnelley and Parsons, 2018 ; Yan et al, 2019 ; Tang et al, 2020a ; Allan et al, 2021 ; Lee et al, 2021 ). In this review, after a brief description of the lessons learned from the previous unsuccessful clinical trials of CF gene therapy in an alignment with recent progress in animal models and viral vectors as tools of gene delivery, we will focus on the major challenges to the implementation of the gene therapy for CF lung disease.…”
Section: Introductionmentioning
confidence: 99%